“We all need to work together on this”: Collectivised approaches to care in Pacific post-separation families - Keil, Moeata (New Zealand Sociology, 2026)
Parental separation has become a common occurrence across the Anglo-West, including New Zealand where this study is based. Much of the literature on post-separation care of children relies on nuclearised understandings of family, focusing on how separated parents care for children and experience post-separation family life. There is limited research on the experience of caring for children in collectivist cultures, including Pacific cultures. Collectivist cultures often adhere to extended family structures and hold communally based understandings of care. In such contexts, caring for children both pre- and post-separation often involves children moving, living and being cared for across multiple households and family members, including their parents, grandmothers, grandfathers, and other family members. Yet, there is a dearth of literature that examines how culturally distinctive modes of doing family that vary across culture and context impacts on how and by whom children are cared for following separation. Drawing on talanoa with 30 Pacific family members involved in children’s everyday post-separation care, this paper examines the actions that Pacific family members undertook to manage and mitigate the challenges experienced by children and parents in post-separation families. In pursuing this inquiry, I pay special attention to how collectivised approaches to caring for children translate into practice, shaping how children are cared for following separation and the meanings that family members attach to their care.